The Implementation of Authentic Assessment in the Literary Subjects: A Pedagogical Perspective - Lalu Muhaimi; Sahuddin Sahuddin; Eka Fitriana; Atri Dewi Azis (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
By applying qualitative approach, this research is aimed at analyzing and describing the planning, processes and evaluation of the implementation of authentic assessment which is carried out comprehensively regarding the whole activity of learning, including the processes and products of the study so that the students’ activities get appraisal. The authentic assessment demands that the students participate in the real and concrete situation and meaningful. The results of the analysis of the data indicate that the literary subjects, that is the topic of this study, are not yet delivered coherently with the aspects and principles of authentic assessment. It is found that most of the literary subjects are presented and evaluated without being made in line with the scientific and systematic study about the nature and application of authentic assessment. Furthermore, with focus on the studies to all aspects of the implementation of authentic assessment on learning literary subjects, the results of this study contribute to the development of science and theory that are applicable to the teaching and learning of literary subjects. In other words, there is a substantial need to apply the concepts and scientific principles of the implementation of authentic assessment in the teaching and learning of all literary subjects with full consideration being given on the appropriate and comprehensive lesson plan.